Metode Perawatan Kesehatan Mental Dalam Islam - Ratnawati, Ratnawati (Institut Agama Islam Negeri (IAIN) Curup, 2019)
This research departs from the problem regarding most people in mental health care businesses who prefer shamanism practices which are generally black magic which is not at all relevant to Islamic teachings. On the other hand that Islam as a religion, contains teachings and complete instructions, including methods of mental health care. This is the main focus of this research, how is the Method of Care for Mental Health in Islam. The purpose of this study was to find concrete and valid data about mental health care in Islam, both in the form of verses of the Qur'an, Hadith or opinions of the scholars, especially those relating to the meaning of mental health and methods of maintaining mental health. The method used in this study is descriptive qualitative with the Religion psychology approach, which is where the psychology of religion functions as a formal object in this study while the verses of the Koran, Hadith and the opinions of the scholars are relevant to the subject matter in the study, is a material object. From all the topics related to the main problem of this research, found that, the relationship between religion and mental health in Islam is a therapy, which lies in the attitude of total surrender to Allah SWT, with complete surrender the peace of mind will be found, which can later be forming a balanced human life in the afterlife. Healthy mental criteria, in Islam are grouped into six categories, namely: Having a positive mental attitude towards himself. Self-actualization. Able to hold integration with existing psychological functions. Able to be autonomous towards yourself (Mandiri). Have an objective perception of the reality that exists. Able to harmonize environmental conditions with yourself. And the last method, that the model of mental health care in Islam is; methods of faith, Islam, and ihsan.